Uso do protocolo no serviço de psicologia e avaliação psicodinâmica em candidatos à cirurgia bariátrica - Paegle, Isabel Cristina Malischesqui (2009)
The Morbid Obesity and Bariatric Surgery clinic demands long term studies and applicant follow-up. The risks and benefits of surgically induced weight loss must serve as a warning beacon for health professionals. The interview usage within the psychology service is a guideline for the psychological therapy. Objectives: 1) Describe the social and demographical profile of the obese patients, applying for the bariatric surgery. 2) Analyze the patients perception about personality characteristics associated with obesity and feeding disorders. 3) Describe the psychodynamic contents of the subject s speech and evaluate the unconscious strain system of two patients, through the Phillipson s Object Relations Test (ORT). Method: methodological planning with data analysis through the epidemiological method and clinical case study, from a psychoanalytical orientation. At the first stage, 300 protocols from the psychological service were consulted and at the second stage, two patients with weight gain were followed after 24 months. They are patients who sought treatment at a specialized health center located in a Brazilian southeastern metropolis, under post-informed consent. The protocols were filled by 227 women and 73 men; average age around 36 years old; 53% of them with college and secondary education; most of them married; BMI between severe and super morbid (94,3%). Appointed surgical techniques Capella Bypass and Fobi- Capella (67%). Results: psychological characteristics mentioned by the patients; anxiety appeared in 93,7% of the answers, followed by hastiness, nervousness, depression, tolerance to frustration, low self-esteem, concern, problem solver (more than 50%). Family history of obesity is present in more than 70%. Depression and alcohol abuse in 30%; psychotherapy attendance (30%) and depression / anxiety control medication (10%). In the second stage, the psychodynamic diagnosis, using the Phillipson s Object Relations Test with two patients, whose analysis showed a need for psychoanalytic sychotherapy, because they had fixations on the schizo-paranoid position and displayed difficulty in dealing with losses and low motivation for change and insight. Conclusions: with the interview superposing and the empyrical observations registration, this semi directed interview script brings better conditions to assess and evaluate the contents disclosed by the patients. The contradictions between the answers and the speech, in the individual contact with the psychologist, point that an investment in preparing the patient for the surgery is needed, and, more acutely, the psychological follow-up in the first post-operatory year. There is a magical thought to be working through during the questionnaire application about beliefs toward the surgery and the weight loss and so invite the patient to fullfil the place of the subject implied in the pre and post operatory process. The Phillipson s ORT contributed to a better understanding of mental functioning of obese patients with weight gain after surgery.(AU)